1999
DOI: 10.1007/s001340050861
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five sedation scoring systems by means of auditory evoked potentials

Abstract: For the assessment of sedation, several scoring systems have been introduced into clinical practice, but the differentiation of deeper sedation levels, especially, remains poor. In this study we compared auditory evoked potentials, as an objective method with which to assess the level of sedation, with five different sedation scoring systems. In comparison with changes in latency of the midlatency component N(b), Ramsay's sedation score showed the closest correlation. Objective electrophysiological monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 18 publications
2
46
0
2
Order By: Relevance
“…In adult patients, Schulte-Tamburen et al [61] found that the Ramsay scale was the clinical scale with the highest correlation with MLAEPs. Doi et al [62] compared the correlations between the Ramsay scale and MLAEPs, BIS and spectral edge frequency, finding the best level of correlation with MLAEPs, followed by the BIS and the spectral edge frequency.…”
Section: Use Of Mlaeps In the Critically Ill Childmentioning
confidence: 99%
“…In adult patients, Schulte-Tamburen et al [61] found that the Ramsay scale was the clinical scale with the highest correlation with MLAEPs. Doi et al [62] compared the correlations between the Ramsay scale and MLAEPs, BIS and spectral edge frequency, finding the best level of correlation with MLAEPs, followed by the BIS and the spectral edge frequency.…”
Section: Use Of Mlaeps In the Critically Ill Childmentioning
confidence: 99%
“…Diferentes escalas são utilizadas para quantificar o grau de sedação. Um estudo de Schulte-Tamburen e col., em 1999 21 , correlacionou cinco sistemas de avaliação de sedação (Escalas de Ramsay, Cohen, Cambridge, Bloomsbury e Newcastle ou Cook) com potenciais evocados auditivos. A melhor correlação foi obtida com a Escala de Ramsay, que classifica os pacientes em graus entre 1 (ansiedade e agitação / inquietude, ou ambos) e 6 (nenhuma resposta) (Tabela I).…”
Section: Agentes Inalatóriosunclassified
“…Different scales a r e u s e d t o q u a n t i f y s e d a t i o n l e v e l . A s t u d y b y Schulte-Tamburen et al, in 1999 21 , has correlated five sedation evaluation systems (Ramsay, Cohen, Cambridge, Bloomsbury and Newcastle or Cook Scales) to auditory evoked potentials. The best correlation was obtained with the Ramsay's Scale, which classifies patients in grades between 1 (anxiety and agitation / unrest or both) and 6 (no response) (Table I).…”
Section: Inhalational Agentsmentioning
confidence: 99%
“…Ramsay sedation scale (RSS; Table 1) and Sedation-agitation scale are widely used as subjective evaluations of the depth of sedation, and the usefulness of these assessment methods are proved 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Auditory evoked potential and oxygen consumption index (V . O 2 I) are the procedures for the objective evaluation of the depth of sedation 3,5 The bispectral index (BIS), has been used to evaluate the anesthetic depth, and the usefulness in the operating room has been established [6][7][8][9][10] . The usefulness of BIS in ICU to evaluate sedation depth is controversial.…”
Section: Introductionmentioning
confidence: 99%